Pembangunan Citra Baru Pada Publik Internal Oleh Manajemen Hotel Bakung Sari Resort And Spa - Artha Pratiwi, N. P. Devinda; Suryawati, IGA Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRAK     Communication is an important role in life, as well as the organization. The most important relationship is a relationship with the internal public. The purpose is to build and maintain relationships have a beneficial between the organization and the employees where success and failure of an organization will depend on the internal public. The management has changed at Bakung Sari Resort and Spa Hotel is led to a name change as well. This name change will form a new image for this hotel. The purpose of this study was to build for a new image taken by the management and see the changes in the internal public, where it is caused by a change of management at the Bakung Sari Resort and Spa Hotel. This study use a qualitative descriptive and use paradigm of positivism also. The results of this study indicate that the strategy is carried out by the change room facilities and the addition of new SPA at the hotel as well as the amenities in each room. The next steps are training, socialization, and focus group discussion can make internal public understand the new image changes that occur. They have outing and gathering that can also tighten silahturami an internal public due to their proximity and a sense of belonging can give a positive image to the external public.   Keywords: Communication Strategy, Image, Internal Public